THE RELATIONSHIP OF SERVICE QUALITY TO OUTPATIENT SATISFACTION AT THE BALOI PERMAI HEALTH CENTER IN 2022 - Farhansyah, Fani; Anisa, Desfa; Tampubolon, Cyntia (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2022)
The aim of this study was to determine the relationship between service quality and satisfaction of outpatients at the Baloi Permai Health Center. The method used is quantitative method with survey research used is cross sectional to determine the effect of health service quality on patient satisfaction at the Baloi Permai Health Center. The results of this study were carried out by a chi square statistical test showing that the quality of patient care at the Baloi Permai Health Center was considered good by 81,2% with a total of 81 respondents. While patients who said they were not good were 18,8% with a total of 19 respondents. Patient Satisfaction at the Baloi Permai Public Health Center who rated satisfaction as much as 68% with a total of 68 respondents. While patients who said they were not good were 32% with a total of 32 respondents. Since the p value is 0,000 <0,05, thereby H0 is rejected and H1 is accepted, thus it can be concluded that there is a relationship between service quality and outpatient patient satisfaction at the Baloi Peria Health Center in 2022.